2013
DOI: 10.1103/physrevb.87.174432
|View full text |Cite
|
Sign up to set email alerts
|

Magnetodynamical response of large-area close-packed arrays of circular dots fabricated by nanosphere lithography

Abstract: We report a combined experimental and theoretical study of the quasistatic hysteresis and dynamic excitations in large-area arrays of NiFe nanodisks forming a hexagonal lattice with the lattice constant of 390 nm. Arrays were fabricated by patterning a 20-nm-thick NiFe film using the etched nanosphere lithography. We have studied a close-packed (edge-to-edge separation between disks dcp = 65 nm) and an ultraclosed packed (ducp = 20 nm) array. Hysteresis loops for both arrays were qualitatively similar and near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 78 publications
(83 reference statements)
0
44
0
Order By: Relevance
“…Together, equations (27) and (37) are the central result of this paper. Using these equations one can calculate the distribution of the internal magnetic field (B i )in the array, equilibrium directions of the magnetic moments in each dot (μ i ), and the spectrum of collective spin wave edge excitations in a semi-infinite array of magnetic nanodots with a complex primitive cell.…”
Section: B Edge Modesmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, equations (27) and (37) are the central result of this paper. Using these equations one can calculate the distribution of the internal magnetic field (B i )in the array, equilibrium directions of the magnetic moments in each dot (μ i ), and the spectrum of collective spin wave edge excitations in a semi-infinite array of magnetic nanodots with a complex primitive cell.…”
Section: B Edge Modesmentioning
confidence: 99%
“…Although the recent progress in the electron and ion beam lithography has made possible the fabrication of arrays of magnetic nanoelements (nanodots) on a large scale 9,[11][12][13]20,22,[25][26][27] , the fabrication of arrays of elements with high aspect ratios (height substantially larger than the radius), which is necessary for the effective dipolar interaction between the elements 22 , still remains a challenging technological problem. Nonetheless, we believe that materials with uniaxial crystallographic anisotropy 28 , like multi-layered composites of CoPt, Co 3 Pt, FePt, CoPd 29 , which exhibit strongly perpendicular static magnetization in the absence of a bias magnetic field, will make possible the physical realization of the magnetic nanodot arrays for signal processing applications in the near future.…”
Section: Novel Magnonicmentioning
confidence: 99%
See 2 more Smart Citations
“…34 However, a detailed investigation of the SEM images at different magnification revealed that the orientation of the symmetry axis suffers a decrease of 25 over the distance of 5.0 mm. 35 The BLS experiments were performed in the Voigt configuration, where the in-plane transferred wave-vector (k) was perpendicular to the external magnetic field applied in the sample plane. The SW dispersion was measured for two different orientations of the magnetic field of l 0 H ¼ 40 mT, as indicated in Figs.…”
mentioning
confidence: 99%